2011
DOI: 10.2174/1876523801104010036
|View full text |Cite
|
Sign up to set email alerts
|

Caffeinated Drinks, Alcohol Consumption, and Hangover Severity

Abstract: This study examined the relationship between consumption of caffeinated beverages and alcohol, and effects on next day hangover severity. In 2010, a survey funded by Utrecht University was conducted among N=549 Dutch students. Beverages consumed on their latest drinking session that produced a hangover were recorded. Hangover severity was scored using the Acute Hangover Scale. No significant correlation between caffeine use and hangover severity was found. Subjects who mixed alcohol with colas consumed signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 14 publications
1
27
1
1
Order By: Relevance
“…Breathalyzer assessment on leaving the bar revealed that BrAC levels were similar in those who consumed alcohol mixed with cola (BrAC 0.108%) or consumed AmED (BrAC 0.106%), and somewhat higher than found in those who consumed alcohol only (BrAC 0.091%). A recent survey confirmed these findings among Dutch students, when reporting on their latest night out that caused a hangover 47. No difference in total alcohol consumption was found between those who consumed alcohol alone or AmED, whereas those who mixed alcohol with cola beverages consumed significantly more alcohol.…”
Section: Resultsmentioning
confidence: 72%
“…Breathalyzer assessment on leaving the bar revealed that BrAC levels were similar in those who consumed alcohol mixed with cola (BrAC 0.108%) or consumed AmED (BrAC 0.106%), and somewhat higher than found in those who consumed alcohol only (BrAC 0.091%). A recent survey confirmed these findings among Dutch students, when reporting on their latest night out that caused a hangover 47. No difference in total alcohol consumption was found between those who consumed alcohol alone or AmED, whereas those who mixed alcohol with cola beverages consumed significantly more alcohol.…”
Section: Resultsmentioning
confidence: 72%
“…Energy drinks are a relatively new mixer option and up until now, only a few comparisons have been made between energy drinks and other popular mixers such as colas. These studies have shown that people who mix alcohol with energy drinks consume less alcohol than people who mix alcohol with colas 19,20. However, these studies had small sample sizes and did not examine the motives for mixing alcohol with specific beverages.…”
Section: Introductionmentioning
confidence: 99%
“…These surveys were conducted among students, and reported that between 6% and 40% of students confirmed consuming AMED at least once 79. Most studies have presented significant correlations between energy drink and alcohol consumption, and reported that those who consumed AMED generally consumed more alcohol and experienced more alcohol-related consequences (eg, driving while intoxicated) than those who consumed alcohol alone 10,11. Other researchers have questioned the methodology of these surveys and the interpretation of the results 1,12,13…”
Section: Introductionmentioning
confidence: 99%